2018
DOI: 10.1063/1.5023878
|View full text |Cite
|
Sign up to set email alerts
|

Neuron dynamics variability and anomalous phase synchronization of neural networks

Abstract: Anomalous phase synchronization describes a synchronization phenomenon occurring even for the weakly coupled network and characterized by a non-monotonous dependence of the synchronization strength on the coupling strength. Its existence may support a theoretical framework to some neurological diseases, such as Parkinson’s and some episodes of seizure behavior generated by epilepsy. Despite the success of controlling or suppressing the anomalous phase synchronization in neural networks applying external pertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…It was shown that the scale-free network displays a non-monotonic evolution of the phase synchronization as the coupling between neurons increases. A similar scenario has been observed in small-world networks, which is called "anomalous phase synchronization" [30,31,55], since the traditional behavior should monotonically transition to PS [33]. Especially, Parkinson's disease and some episodes of seizure behavior generated by epilepsy may be associated to anomalous synchronization.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…It was shown that the scale-free network displays a non-monotonic evolution of the phase synchronization as the coupling between neurons increases. A similar scenario has been observed in small-world networks, which is called "anomalous phase synchronization" [30,31,55], since the traditional behavior should monotonically transition to PS [33]. Especially, Parkinson's disease and some episodes of seizure behavior generated by epilepsy may be associated to anomalous synchronization.…”
Section: Discussionmentioning
confidence: 52%
“…We showed the existence of a threshold, 2000 neurons (40% of the network), which must be disturbed to reach the suppression of anomalous PS in all cases. Such a conclusion implies that the synchronization is related to the individual dynamics of each neuron rather than the network topology [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations